Village planning in the primitive world - Fraser, Douglas (New York : Brazille, 1968)
Contenido: Mbuti Pygmies, Bushmen, Cheyenne indians, Nueva Guinea, Africa, Nigeria
Keywords: URBANISMO; HISTORIA; PLANIFICACION URBANA; CIUDADES; CIUDADES PRIMITIVAS